Are intestinal helminths playing a positive role in tuberculosis risk? A systematic review and meta-analysis - Taghipour, Ali; Mosadegh, Mehrdad; Kheirollahzadeh, Fatemeh; Olfatifar, Meysam; Safari, Hossein; Nasiri, Mohammad Javad; Fathi, Atefeh; Badri, Milad; Piri Dogaheh, Hadi; Azimi, Taher (PloS one, 2019)
Co-infection of intestinal helminthic infections (IHIs) and tuberculosis (TB) has appeared as a public health issue, especially in developing countries. Some recent studies have been carried out on the possible relevance of IHIs to TB. The current systematic review and meta-analysis was conducted to assess the prevalence and odds ratio (OR) of IHIs among TB patients and clarify the relationship between IHIs and TB disease. For the purpose of the study, five English databases including PubMed, Science Direct, Scopus, Web of Science (ISI), and Google scholar were searched (up to January 30, 2019) in order to find the related studies. Random-effects meta-analysis model was used to estimate the pooled prevalence, odds ratio (OR), and 95% confidence interval (CI). Inclusion and exclusion criteria were applied. A total of 20 studies including 10 studies with case-control design (2217 patients and 2520 controls) and 10 studies with cross-sectional design (a total of 2415 participants) met the eligibility criteria. As shown by the random-effects model, the pooled prevalence of IHIs in TB patients was estimated to be 26% (95% CI, 17-35%; 1249/4632). The risk of IHI was higher in TB patients compared to controls but this was not statistically significant. However, according to genus/species, the pooled OR of Strongyloides stercoralis (S. stercoralis) (OR, 2.68; 95% CI, 1.59-4.54) had a significantly higher risk in TB patients compared to controls. Nevertheless, the results of random effects model showed no statistically significant association between overall pooled OR of IHIs in TB patients compared to controls in case-control studies (OR, 1; 95% CI, 0-1). It is highly recommended that more precise studies should be carried out by researchers in order to better understand this association. Also, it is of great importance to include the periodic screenings for IHIs in the routine clinical care of these patients.